Electro-deposited nanocomposite coatings and their behaviours against aqueous and high-temperature corrosion: A review - M.O. Egbuhuzor; C.O. Akalezi; S.B. Ulaeto; D.I. Njoku; B.I. Onyeachu; E.E. Oguzie (Hybrid Advances, 2024)
Nanocomposite coatings have recently gained tremendous attention and consideration in corrosion prevention due to their mechanical and physiochemical properties. These properties have influenced the behaviour of the nanocomposite coatings in aqueous and high-temperature environments. Electrodeposition is a cheap electrochemical technique used to modify the surface structure of materials and produce high-quality nanocomposite coatings. In this review, electro-deposited nanocomposites, processing methods and electrodeposition of nanocomposite coating were studied. Also, the corrosion behaviour of some of these nanocomposite coatings in aqueous and high temperatures was extensively reviewed.